Individualized Repetitive Transcranial Magnetic Stimulation Treatment in Chronic Tinnitus? - Kreuzer, Peter M.; Poeppl, Timm B.; Rupprecht, Rainer; Vielsmeier, Veronika; Lehner, Astrid; Langguth, Berthold; Schecklmann, Martin (Frontiers in Neurology, 2017)
Background: Prefrontal and temporo-parietal repetitive transcranial magnetic stimulation (rTMS) in patients suffering from chronic tinnitus have shown significant but only moderate effectiveness with high inter-individual variability in treatment response. This open-label pilot study was designed to examine the general feasibility of an individualized fronto-temporal rTMS protocol and to explore what criteria are needed for a more detailed evaluation in randomized clinical studies. Methods: During the first session of a two-week rTMS protocol, we applied different rTMS protocols to the left and right temporo-parietal and dorsolateral prefrontal cortex (DLPFC) in 25 tinnitus patients. Short trains of 1Hz, 5Hz, 10Hz, 20Hz and cTBS (continuous theta burst stimulation) were applied and patients were asked for immediate tinnitus reductions after each train. If a patient reported such improvements rTMS treatment was applied over 9 sessions with a combined protocol consisting of the most effective frontal and the most effective temporo-parietal stimulation protocol. Those patients who did not improve after the test session were treated with a standard prefrontal plus temporo-parietal protocol (20 Hz over left DLPFC + 1Hz over temporo-parietal cortex). Results: Almost half of the patients (12 out of 25) reported immediate tinnitus reductions during the test session. In this group the mean pre-to-post-treatment amelioration in the tinnitus questionnaire was higher (medium to high effect sizes) in contrast to the patients who did not respond to the test session. Treatment outcome remained stable over a follow-up period of ten weeks. Discussion: Individualized rTMS was shown to be feasible and effective in chronic tinnitus. The results obtained from this study provide tentative evidence in support of for an individualized rTMS treatment approach and might provide a basis for a “tailored” application of rTMS in tinnitus and other neuropsychiatric disorders.